Macroeconomic Equity: Addressing Income Inequality And Social Justice Through Economic Policy - Vikas Kumar (Revista Electronica de Veterinaria, 2024)
The purpose of this paper will be to discuss the status, policies, and prospects of economic development and income distribution in the existing literature. The research aim is to understand the determinants of global and national income distribution, analyse prior data, and assess the effectiveness of different policies in combating inequality. Emphasis is placed on the taxation system, social insurance, labor market, and education and health care reforms. The study therefore calls for the use of good growth practices, international collaboration, and the use of creativity in the fight against inequality and injustice. The results of the study imply that some practices and minorities’ integration are essential for the decrease of the gap and the formation of an equal economy.